My grandmother's hands : racialized trauma and the pathway to mending our hearts and bodies - Menakem, Resmaa (2017)
"The body is where our instincts reside and where we fight, flee, or freeze, and it endures the trauma inflicted by the ills that plague society. In this groundbreaking work, therapist Resmaa Menakem examines the damage caused by racism in America from the perspective of body-centered psychology. He argues this destruction will continue until Americans learn to heal the generational anguish of white supremacy, which is deeply embedded in all our bodies. Our collective agony doesn't just affect African Americans. White Americans suffer their own secondary trauma as well. So do blue Americans -- our police. My Grandmother's Hands is a call to action for all of us to recognize that racism is not about the head, but about the body, and introduces an alternative view of what we can do to grow beyond our entrenched racialized divide."--Amazon.com
Do not cross this line -- Watch your body -- Acknowledging our ancestors -- Our bodies, our country -- Unarmed and dismembered . Your body and blood ; Black, white, blue, and you ; Body to body, generation to generation ; European trauma and the invention of whiteness ; Assaulting the black heart ; Violating the black body ; The false fragility of the white body ; White-body supremacy and the police body ; Changing the world begins with your body -- Remembering ourselves. Your soul nerve ; Settling and safeguarding your body ; The wisdom of clean pain ; Reaching out to other bodies ; Harmonizing with other bodies ; Mending the black heart and body ; Mending the white heart and body ; Mending the police heart and body -- Mending our collective body. Body-centered activism ; Creating culture ; Cultural healing for African Americans ; Whiteness without supremacy ; Reshaping police culture ; Healing is in our hands ; The reckoning -- Afterword -- Five opportunities of healing and making room for growth
Includes bibliographical references
Keywords: African Americans -- Social conditions; Whites -- Race identity -- United States; African Americans; Social Conditions; Race Relations; European Continental Ancestry Group; United States -- Race relations; United States